(5x-10) (x-1)=(3x-2)la2+7-(2x+1) la2
Răspunsuri la întrebare
Răspuns de
1
(5x-10) (x-1)=(3x-2)la2+7-(2x+1) la2
5x^2-5x-10x+10 = 9x^2-2*3x*2+4 + 7 - (4x^2+4x+1)
5x^2-15x+10 = 9x^2-12x+11 - 4x^2-4x-1
5x^2-15x+10 = 9x^2-12x+11 - 4x^2-4x-1
5x^2-9x^2+4x^2 - 15x+12x+4x = 11-1-10
x=11-1-10
x=0
5x^2-5x-10x+10 = 9x^2-2*3x*2+4 + 7 - (4x^2+4x+1)
5x^2-15x+10 = 9x^2-12x+11 - 4x^2-4x-1
5x^2-15x+10 = 9x^2-12x+11 - 4x^2-4x-1
5x^2-9x^2+4x^2 - 15x+12x+4x = 11-1-10
x=11-1-10
x=0
CosmoteRo:
(4xla 2+4x+1)...(4)
Răspuns de
0
(5x-10)(x-1)=(3x-2) la 2 +7-(2x+1) la 2
5x la 2-5x-10x+10=9x la 2-12x+4+7-4x la 2 -4x-1
5x la 2-15x+10=5x la2-16x +10
5x la 2-5x la 2-15x+16x=10-10
x=0
5x la 2-5x-10x+10=9x la 2-12x+4+7-4x la 2 -4x-1
5x la 2-15x+10=5x la2-16x +10
5x la 2-5x la 2-15x+16x=10-10
x=0
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Geografie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă